Lifetime exposure to particulate air pollutants is negatively associated with lung function in non-asthmatic children. (May 2018) - Tsui, Hung-Chang; Chen, Chi-Hsien; Wu, Ying-Hsuan; Chiang, Hung-Che; Chen, Bing-Yu; Guo, Yue Leon
Abstract: Background: Pulmonary function is known to be affected by acute and subacute exposure to ambient air pollution. However, the impacts of lifetime exposure to air pollution on the pulmonary function of children have been inconsistent. The present study investigated the impact of lifetime residential exposure to intermediate levels of air pollution on the pulmonary function of schoolchildren. Methods: In 2011, a survey of children aged 6–15 years was conducted in 44 schools in Taiwan. Atopic history, residential history, and environmental factors were recorded. Spirograms were obtained from a random sample of children without asthma. A total of 535 girls and 481 boys without a history of asthma were enrolled. Lifetime residential exposure to air pollutants, including particulate matter with an aerodynamic diameter less than 10 μm (PM10 ), ozone (O3 ), sulfur dioxide (SO2 ), nitrogen dioxide (NO2 ), and carbon monoxide (CO), was estimated using the kriging method, based on monitored data from the Taiwan Environmental Protection Administration. Multiple linear regression was used to analyze the association between lifetime air pollution exposure and pulmonary function, after adjustment for potential confounders and recent exposure. Results: After adjustment for 7-day average air pollutant levels, a 10 μg/m 3 increase in PM10 was related to reductions in the forced expiratory volume in 1 s (−2.00%; 95% confidence interval [CI] −3.09% to −0.90%), forced vital capacity (−1.86%; CI: −2.96% to −0.75%), and maximal midexpiratory flow (−2.28%; CI: −4.04% to −0.51%). These associations were independent of the other pollutants. Conclusion: Lifetime exposure to 25–85 μg/m 3 of PM10 has negative impacts on the pulmonary function of children. Graphical abstract: Image 1 Highlights: A survey of children aged 6–15 years was conducted in 44 schools in Taiwan. The lifetime residential exposure to 5 air pollutants was estimated by kriging method. The association between lung function and lifetime exposure was analyzed. Children's lung function is negatively associated with lifetime exposure to PM10 . Abstract : This study provides documentation that lifetime exposure to 25–85 μg/m 3 of PM10 reduces the pulmonary function of schoolchildren, after adjustment for short-term exposure.